2018
DOI: 10.3892/mmr.2018.9087
|View full text |Cite|
|
Sign up to set email alerts
|

Tanshinone IIA regulates colorectal cancer apoptosis via attenuation of Parkin‑mediated mitophagy by suppressing AMPK/Skp2 pathways

Abstract: Mitophagy is important for cancer development. Notably, the role of Parkin‑mediated mitophagy in colorectal cancer (CRC) mortality has not been fully determined. Therefore, the present study aimed to investigate the effect of Parkin‑mediated mitophagy on CRC apoptosis. In addition, the present study investigated the therapeutic effects of Tanshinone IIA (Tan IIA) on the regulation of CRC cell death via mitophagy. Cellular apoptosis was measured following Tan IIA treatment. In addition, mitophagy activity was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 71 publications
0
27
0
Order By: Relevance
“…no. 568–72-9) were incubated with cells for approximately 12 h. This concentration range was selected based on a previous study [ 36 ]. Meanwhile, the cells incubated with PBS were used as the control group.…”
Section: Methodsmentioning
confidence: 99%
“…no. 568–72-9) were incubated with cells for approximately 12 h. This concentration range was selected based on a previous study [ 36 ]. Meanwhile, the cells incubated with PBS were used as the control group.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Tan IIA might induce the autophagy in oral squamous cell carcinoma by both activating the Beclin-1/Atg7/Atg12-Atg5 pathway and inactivating the PI3K/Akt/mTOR pathway (Ye et al, 2018). Another recent study proved that Tan IIA suppressed colorectal cancer cell growth, decreased mitochondrial membrane potential, and inhibited mitophagy through inactivation of AMPK/Skp1/Parkin pathway (He and Gu, 2018).…”
Section: Tan Iia Induces Tumor Cell Autophagymentioning
confidence: 98%
“…In another research, Tan IIA increased p53, p21, and Bax; decreased B-cell lymphoma-2 (Bcl-2), cell division cycle gene 2 (cdc2), and cdc25 expression; and induced ER-related apoptosis in hepatocellular carcinoma 15 cells through the regulation of calreticulin, caspase-12, and GADD153 expression (Cheng and Su, 2010). Additionally, Tan IIA inhibited the protective mitophagy through the inhibition of the adenosine monophosphate-activated kinase (AMPK), S-phase kinase-associated protein 2 (Skp2), Parkin pathway, leading to the mitochondria-mediated apoptosis of cancer cells (He and Gu, 2018).…”
Section: Tan Iia Inhibits Tumor Cell Growth and Proliferationmentioning
confidence: 99%
“…Many studies have demonstrated that Tan IIA results in an increased apoptosis rate in NSCLC (Chiu & Su, ), and colorectal carcinoma (He & Gu, ). Furthermore, Zhao found that Tan IIA could potentiate the apoptosis rate of DDP in pharyngeal squamous cell carcinoma (Zhao et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Tan IIA is prescribed for the treatment of cardiovascular disease in the pharmacopoeia of the People's Republic of China as the TCM “Danshen.” Tan IIA has been shown to exhibit antiangiogenic (Tsai, Yang, Wu, Pang, & Huang, ), antioxidant (Guo et al, ), anti‐inflammatory, immunomodulatory (Chen & Xu, ), and antitumor activities. A number of studies have shown that Tan IIA antagonizes the proliferation of multiple human cancer cell lines, such as human colorectal cancer (He & Gu, ; Sui et al, ), human gastric carcinoma (Su, ; Zhang et al, ), human pancreatic cancer (Chiu & Su, ), human breast cancer and (Li & Lai, ; Lv et al, ), and human osteosarcoma cells (Huang et al, ). However, the specific mechanisms of action underlying the anticancer effects of Tan IIA in NSCLC cells remain elusive.…”
Section: Introductionmentioning
confidence: 99%